ENHANCING MILLING PERFORMANCE OF 6061 ALUMINUM ALLOY WITH NANOCUTTING FLUID AND MQL - Tosun, Nihat; Rasul, Sleman Yahya; Mahmat, Aybars; Tosun, Gul (World Scientific Publ Co Pte Ltd, 2024)
During the machining of aluminum alloys, the adhesion of chips to the tool affects the performance characteristics. Today, different cooling systems are used to eliminate these negativities. In this study, the effects of end milling using HSS and carbide cutting tools of 6061-T6 aluminum alloy on surface roughness, chip thickness ratio and tool wear were examined using different cooling techniques (dry, minimum quantity lubrication (MQL) and nanocutting fluid). Different cutting speeds (180, 200, 220 m/min) and different feed rates (0.05, 0.06, 0.07 mm/rev) were used in the experiments. According to experimental findings, tool wear and surface roughness decreased at low cutting speed and feed rate by using nanocutting fluid with carbide cutting tools. It has been observed that the chip thickness ratio increases with high cutting speeds using nanocutting fluid and decreases with dry machining and high feed rates. The best milling performance of the aluminum alloy was achieved in experiments using carbide cutting tools and nanocutting fluid.
Keywords: MQL; nanofluid; surface roughness; wear; chip; aluminum; milling